Production of milk foams by steam injection: The effects of steam pressure and nozzle design. (December 2015) - Jimenez-Junca, Carlos; Sher, Alexander; Gumy, Jean-Claude; Niranjan, K.
Highlights: Links between injector design, steam pressure and milk foam quality are reported. Unconfined jets produce foams having superior texture and stability. Steam pressure influences foam quality more in the case of confined jet sparger. Foam liquid drainage is function of gas hold-up multiplied by mean bubble diameter. Abstract: Foam properties depend on the physico-chemical characteristics of the continuous phase, the method of production and process conditions employed; however the preparation of barista-style milk foams in coffee shops by injection of steam uses milk as its main ingredient which limits the control of foam properties by changing the biochemical characteristics of the continuous phase. Therefore, the control of process conditions and nozzle design are the only ways available to produce foams with diverse properties. Milk foams were produced employing different steam pressures (100–280 kPa gauge) and nozzle designs (ejector, plunging-jet and confined-jet nozzles). The foamability of milk, and the stability, bubble size and texture of the foams were investigated. Variations in steam pressure and nozzle design changed the hydrodynamic conditions during foam production, resulting in foams having a range of properties. Steam pressure influenced foam characteristics, although the net effect depended on the nozzle design used. These results suggest that, in addition to the physicochemical determinants of milk, the foam properties can also be controlled by changing the steam pressure and nozzle design.